Spread Of Pterygium Disease In Khorezm Region - Radjabov Hamid Rashid ugli. (Zien Journals, 2022)
Pterygium is a conjunctival-corneal degeneration, accompanied by the growth of fibrovascular tissue along the surface of the cornea. Presumably, the most important provoking factor is ultraviolet radiation. In addition, the influence of factors such as changes in the tear film, imbalance of cytokines, growth factors, immunological mechanisms, genetic mutations, as well as viral diseases is being studied. However, there may be such manifestations of dry eye syndrome as itching, burning, or lacrimation caused by uneven moisture in the ocular surface. Further spread of the pterygium into the optical zone reduces visual acuity and requires surgical treatment. Countries close to the equator (countries with high UV exposure) and people working with dust have 18-20% more cases of the disease than other countries. The study found that out of 1081 patients with pterygium disease, 355 were women and 724 were men. When studying the disease in cities and regions, it turned out that it is more common in the city of Urgench and in people aged 40-65 years. As a recommendation, the prevention of any disease, less walks in the light of the sun, dusty air and compliance with the rules of hygiene, as well as the timely conduct of comprehensive medical examinations are a necessary factor in the prevention of any disease for human health.
Keywords: pterygium; elastoid dysplasia; proliferative; fibromatosis